CRISPR/Cas9-Induced Loss of Keap1 Enhances Anti-oxidation in Rat Adipose-Derived Mesenchymal Stem Cells - Hu, Yiling; Liu, Shubao; Zhu, Bing-Mei (Frontiers in Neurology, 2020)
Stem cells have become powerful tool in the treatment of many diseases due to their regenerative ability, and rapidly they promote development of regenerative medicine, such as traumatic brain injury. However, the high level of oxidant micro-environment in lesion region lead more than 99% cells into death. In this study, we used genetic methods to edit Keap1 gene in mesenchymal stem cells and observed their antioxidative ability. First we disturbed the start codon and the 376th amino acid codon of Keap1 in adipose-derived mesenchymal stem cells (Ad-MSCs) with CRISPR/Cas9 respectively, to release Nrf2 from the binding of Keap1. As a result, Nrf2 was activated and localized into nuclei and regulated cellular anti-oxidation. We observed that the cells lacking Keap1 ATG codon showed obvious nuclear localization of Nrf2. Besides lower expression of Bax-1 and lower content of MDA were detected after H2O2 treatment, we also found higher expression of Bcl-2 in Keap1 ATG codon knock-out cells, whereas, a higher expression of PCNA was observed only in the Keap1 376th codon edited cells, whose Bax-1 expression was lower than the control cells. Our study revealed that loss of Keap1 resulted in anti-oxidative ability in Ad-MSCs, suggesting that our strategy can hopefully increase the viability of mesenchymal stem cells after grafting. This study is also a frontier exploration to the application of CRISPR/Cas9 in Ad-MSCs.